2014
DOI: 10.1161/hypertensionaha.114.03603
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypoxia and Hypercapnia Inhibit the Hypothalamic Paraventricular Nucleus Neurotransmission to Parasympathetic Cardiac Neurons in the Brain Stem

Abstract: Obstructive sleep apnea is associated with chronic intermittent hypoxia/hypercapnia (CIHH) episodes during sleep that heighten sympathetic and diminish parasympathetic activity to the heart. While one population of neurons in the paraventricular nucleus of the hypothalamus strongly influence sympathetic tone and have increased activity following CIHH, little is known about the role of this pathway to parasympathetic neurons, and how this network is altered in CIHH. We hypothesized that CIHH inhibits the excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
(53 reference statements)
2
31
0
Order By: Relevance
“…Although brainstem slices that contained CVNs in the DMV did not include the cell bodies of ChR2-EYFP-expressing orexin neurons it has been previously shown that light-triggered transmitter release from ChR2-EYFP-expressing fibers occurs in the absence of the ChR2-EYFP-expressing cell bodies (Pinol et al, 2012, Schone et al, 2012, Dergacheva et al, 2014). Photostimulation of ChR2-EYFP fibers with brief light pulses (3 ms) generated fast post-synaptic responses in 16 out of 44 CVNs tested (36%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although brainstem slices that contained CVNs in the DMV did not include the cell bodies of ChR2-EYFP-expressing orexin neurons it has been previously shown that light-triggered transmitter release from ChR2-EYFP-expressing fibers occurs in the absence of the ChR2-EYFP-expressing cell bodies (Pinol et al, 2012, Schone et al, 2012, Dergacheva et al, 2014). Photostimulation of ChR2-EYFP fibers with brief light pulses (3 ms) generated fast post-synaptic responses in 16 out of 44 CVNs tested (36%).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the activity CVNs in the DMV protects the heart from ischemia/reperfusion injury independent of changes in heart rate (Mastitskaya et al, 2012). The activity of CVNs in the DMV are strongly influenced by neurotransmission from other neurons in the brainstem, as well as pathways from the locus coeruleus and oxytocin neurons in the hypothalamus (DePuy et al, 2013, Dergacheva et al, 2014, Pinol et al, 2014, Wang et al, 2014). The results from immunohistochemical studies indicate orexin neurons could be another important source of innervation to neurons in the DMV (Peyron et al, 1998, Date et al, 1999).…”
mentioning
confidence: 99%
“…These four populations of GABAergic neurons were retained in the brain stem slice preparation used in this study and are the probable source of the GABAergic neurons that directly project to CVNs that are facilitated in LVH animals. There are two known major sources of excitatory input to CVNs: one originates from neurons in the NTS (27), and the other is an excitatory pathway from neurons in the hypothalamic paraventricular nucleus (PVN) (9,29,30). The NTS receives primary information from cardiorespiratory sensory neurons, and the excitatory pathway from the NTS to CVNs likely plays an essential role in the chemoreceptor and baroreceptor reflex control of heart rate (1).…”
Section: Discussionmentioning
confidence: 99%
“…These two brain areas activate peripheral chemoreceptors and deactivate baroreflex sensitivity, favoring an additional rise of the sympathetic tonus and a fall of parasympathetic tone. The altered balances between cardioprotective parasympathetic activity and enhanced sympathetic tonus result in tachycardia, decreased baroreflex sensitivity, and a rise in BP and cardiovascular risk 89. These consequences are explained by the effect of GABAergic mechanisms that exert an inhibitory effect on parasympathetic cardiac vagal neurons,90 and orexin-A acting on parasympathetic control of the heart rate 91.…”
Section: Deleterious Effects Of Cih: the Osa Modelmentioning
confidence: 99%